Dakwah Pemberdayaan Umat Perspektif Al-Qur`an - Hassan Zaeni; Hasan Mukmin; Sultan Syahril; Fitri Yanti; Aswadi Aswadi (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
This article aims to find out about: How the concept of preaching empowerment of the perspective of the Qur'an. This research is a type of library (library research) using the Thematic Interpretation approach. With the main source being the Qur'an, and focused on seven verses relating to da'wah and empowerment. And secondary sources in the form of books or books relating to the problem to be answered in this study. The results of this study reveal that the concept of empowering the people of The Qur'an perspective as follows. First, the mission of community empowerment aims to invite, order, direct, motivate to guide the target community (mad'u) to jointly make changes for the better oriented towards empowering and community independence, in order to realize shared happiness in the afterlife. Second, the context of empowerment in the Qur'an includes all aspects of both lahiriyah (material) and ruhiyah. In the lahiriyah aspect, it is carried out in the form of the construction of supporting facilities for community independence. In the aspect of empowerment, it is carried out in the form of education, recitation, etc. Third, the desired changes in the community will not be possible unless they start from each other by protecting and maintaining and developing their potential and environment that has been bestowed by Allah. Artikel ini bertujuan untuk mengetahui tentang bagaimana konsep dakwah pemberdayaan umat perspektif al-Qur’an. Penelitian ini merupakan jenis pustaka (library resech), dengan menggunakan pendekatan Tafsir Tematik. dengan sumber utama adalah al-Qur’an, dan terfokus pada tujuh ayat yang berkaitan dengan dakwah dan pemberdayaan. Dan sumber skunder berupa kitab-kitab atau buku yang berkaitan dengan masalah yang akan dijawab pada penelitian ini. Hasil penelitian ini mengungkapkan bahwa konsep dakwah Pemberdayaan umat perspektif al-Qur’an sebagai berikut. Pertama dakwah pemberdayaan umat bertujuan untuk mengajak, menyuruh, mengarahkan, momotivasi membimbing masyarakat sasaran (mad’u) untuk bersamasama melakukan perubahan ke arah yang lebih baik yang berorientasi pada pemberdayaan dan pemandirian masyarakat, dalam rangka mewujudkan kebahagian bersama di dunia akhirat. Kedua, Konteks pemberdayaan dalam al-Qur’an mencakup seluruh aspek baik lahiriyah (material) maupun ruhiyah. Pada aspek ahiriyah dilakukan dalam bentuk pembangunan sarana-sarana penunjang kemandirian masyarakat. Pada aspek ruhiyah pemberdayaan dilakukan dalam bentuk pendidikan, pengajian dan lainya Ketiga, Perubahan yang diinginkan di masyarakat, tidak mungkin akan tejadi kecuali dengan dimulai dari diri masing-masing dengan cara menjaga dan memelihara serta mengembangkan potensi diri dan lingkungannya yang telah dianugrahkan oleh Allah Swt.